Acetylcorynoline Impairs the Maturation of Mouse Bone Marrow-Derived Dendritic Cells via Suppression of IκB Kinase and Mitogen-Activated Protein Kinase Activities - Fu, Ru-Huei (Public Library of Science, 2013)
BACKGROUND: Dendritic cells (DCs) are major modulators in the immune system. One active field of research is the manipulation of DCs as pharmacological targets to screen novel biological modifiers for the treatment of inflammatory and autoimmune disorders. Acetylcorynoline is the major alkaloid component derived from Corydalis bungeana herbs. We assessed the capability of acetylcorynoline to regulate lipopolysaccharide (LPS)-stimulated activation of mouse bone marrow-derived DCs. METHODOLOGY/PRINCIPAL FINDINGS: Our experimental data showed that treatment with up to 20 µM acetylcorynoline does not cause cytotoxicity in cells. Acetylcorynoline significantly inhibited the secretion of tumor necrosis factor-α, interleukin-6, and interleukin-12p70 by LPS-stimulated DCs. The expression of LPS-induced major histocompatibility complex class II, CD40, and CD86 on DCs was also decreased by acetylcorynoline, and the endocytic capacity of LPS-stimulated DCs was restored by acetylcorynoline. In addition, LPS-stimulated DC-elicited allogeneic T-cell proliferation was blocked by acetylcorynoline, and the migratory ability of LPS-stimulated DCs was reduced by acetylcorynoline. Moreover, acetylcorynoline significantly inhibits LPS-induced activation of IκB kinase and mitogen-activated protein kinase. Importantly, administration of acetylcorynoline significantly attenuates 2,4-dinitro-1-fluorobenzene-induced delayed-type hypersensitivity. CONCLUSIONS/SIGNIFICANCE: Acetylcorynoline may be one of the potent immunosuppressive agents through the blockage of DC maturation and function.